Interlayer-expanded 2D VS2 for fast response/recovery NO2 detection at low-temperature - Wang, Huajing; Xiong, Rui; Yang, Huimin; Qin, Ziyu; Sa, Baisheng; Wu, Xiao; Xie, Changsheng; Zeng, Dawen (Applied surface science, 2022)
Here, by means of opening the interlayer spacing (5.8 Å to 10 Å), enhanced gas response (∼2 to 50 ppm NO2) and fast response/recovery speed (∼15 s) can be simultaneously achieved in the novel VS2-E based gas sensor, because of the enlarged distance allows more NO2 to enter the interlayer, and the weaker binding energy (−0.22 eV) of NO2 in the expanded VS2-E layers accelerates its adsorption and desorption. [Display omitted] •A novel NO2 sensor based on expanded 2D VS2 is reported for its fast response/recovery (15 s).•Revealing the p-type semiconducting features of the expanded VS2 with coexistence of T and H phases.•Confirming that enlarging the interlayer spacing can improve the gas-sensing properties of 2D TMDs innovatively.•In-depth explanations are supported by the DFT calculations and the mechanism explanation. Currently, most gas sensors of two-dimensional (2D) layered transition metal dichalcogenides (TMDs) are only focused on the surface adsorption while ignoring their large interlayer active regions. The recovery time of 2D TMDs gas sensors are relatively long due to the limited interlayer spacing. Herein, the interlayer-expanded VS2 (VS2-E, 10 Å) based NO2 gas sensor with rapid response/recovery (∼15 s) is reported innovatively. The response and recovery time is 1/23 and 1/41 of the normal interlayer spacing VS2 (VS2-N, 5.8 Å) counterparts, respectively. VS2-E with coexistence of T and H phases shows the p-type semiconductor features. In addition, the response value of VS2-E sensor is ∼2 to 50 ppm NO2 at 120 °C, approximately twice that of VS2-N. The enlarged interlayer spacing of VS2-E promotes the adsorption/desorption of more NO2 molecules between the interlayers, leading to a larger response and quicker response/recovery for VS2-E compared with VS2-N. This is also confirmed by a weaker binding energy (−0.17 eV) of NO2 in VS2-E layers than that of VS2-N (−0.62 eV) calculated by theoretical calculation. This work enriches the interlayer sensing mechanism and provides a significant guidance for the applications of interlayer regulation engineering in other 2D layered gas-sensing materials.